Testing Utility of Organogeochemical Proxies to Assess Sources of Organic Matter, Paleoredox Conditions, and Thermal Maturity in Mature Marcellus Shale - Agrawal, Vikas; Sharma, Shikha (Frontiers in Energy Research, 2018)
It is generally accepted that in mature shales, biomarkers and pyrolysis proxies are not very helpful in understanding the source/type of organic matter (OM), paleo-redox conditions during deposition and thermal maturity. The purpose of the study study was conducted to test the efficacy of these proxies in mature Marcellus shale (VRo> 1). Samples were collected from oil-prone (WV-7) and gas-prone (WV-6) wells in Wetzel and Monongalia Counties, West Virginia, respectively. These wells were chosen for this test study because high-resolution geochemical and isotopic studies have previously been conducted on these cores and depositional model had been proposed. The model suggests that sediments in WV-6 well are more mature, received higher terrestrial OM influx and were deposited in less anoxic environment as compared to WV-7 well. We used an improved method to extract the small amount of biomarkers preserved in the samples. Further, the extracts were analyzed by a high-resolution GC×GC FID method to quantify the distribution of aliphatic biomarkers. The hydrogen and oxygen indices (HI vs. OI plot) determined by Source Rock Analysis could not be used to determine the kerogen type due to their very low values. However, interpretations were derived from S1 vs. S2 and S2/S3 vs. TOC cross plots, thermal maturity parameter (Tmax), fraction conversion of OM to hydrocarbon (HC), and residual carbon/pyrolysable carbon (RC/PC) ratio. The conclusions drawn from the biomarkers and SRA data are in agreement with the HC production data from these wells as well as interpretations derived from geochemical and isotopic studies conducted on these core. Therefore, we propose that despite some limitations biomarker and pyrolysis proxies can be used to determine the thermal and depositional history of mature shales like the Marcellus Shale.